اتّجاهات سيّد قطب وحمكا في استخراج الدروس والعبر من الآيات المتعلّقة بأحداث السيرة النبوية: دراسة مقارنة في تفسيريهما: The trends of Sayyid Qutb and HAMKA in extracting the highlights and lessons from the verses related to the events of Prophetic history: a comparative study in their exegeses - Ismail, Mohd Arubi; Mohd , Nadzirah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
تناولت هذه الدراسة اتّجاهات المفكّر الإسلامي المصري سيّد قطب والمفكّر الإسلامي الإندونيسي حمكا في استخراج الدروس والعبر من الآيات المتعلّقة بأحداث السيرة النبوية المختارة، وتعرّضت لأوجه الاتّفاق وأوجه الاختلاف بين اتّجاهات هذين المفسّرَين. وتظهر أهمية الدراسة في أنها اتّخذت اتّجاهات المفسّرَين من المدرسة الاجتماعية التي تمسّ القضايا المعاصرة والمستجدة كثيرًا في التفسير، فلعلّ الاتّجاهات المستفادة من تفسيريهما ستكون محلّ الاهتمام والاقتداء في إحياء فقه السيرة المستنبط من القرآن وجعله مناسبًا للتطبيق في الواقع. واستخدم الباحثان المنهج الوصفي التحليلي لتوضيح المراد بالاتّجاهات والسيرة النبوية، ولبيان ترجمة المفسرين ومنهجهما في التفسير، ولتحليل اتّجاهاتهما في استخراج الدروس والعبر. ووظّف الباحثان المنهج المقارن أيضا لاكتشاف أوجه الاتّفاق وأوجه الاختلاف بين اتّجاهات المفسّرين. وقد توصّلت الدراسة إلى أن المفسّرين اتّفقا في الاتّجاه الدعوي، والاتّجاه العقدي، واستظهار الحِكَم والأسباب أو الدلالات، والتنزيل الواقعي. وانتهت الدراسة إلى أن المفسّرين اختلفا في بعض الاتّجاهات حيث تفرّد سيّد قطب عن حمكا في إبراز حقائق الإسلام وتصوّراته، وتميّز حمكا عن سيّد قطب بالاتّجاه السياسي، والاتّجاه السلوكي، وبيان الأحكام الفقهية. This study dealt with the trends of the Egyptian Islamic thinker Sayyid Qutb and the Indonesian Islamic thinker HAMKA in extracting highlights and lessons from the verses related to the selected events of Prophetic history, and examined the similarities and differences between these exegetes’ trends. The importance of this research appears because of it takes the trends of the exegetes from the social approach school of Qur’anic exegesis that touches on many contemporary and emerging issues. Perhaps the trends obtained from their exegeses will be the subject of interest and emulation in reviving the reflection of Prophetic history derived from the Qur’ān and making it relevant to be applied in present time. The researchers used the descriptive-analytical approach to clarify what is meant by Al-Ittijāhāt and Al-Sīrah Al-Nabawiah, to introduce the biography of the both exegetes and their approach in exegeses, and to analyze their trends in extracting highlights and lessons. The researchers also used the comparative method to discover the similarities and the differences between the exegetes' trends. The study concluded that both exegetes agreed on the trends in the Islamic propagation direction, the Islamic faith direction, the finding of appropriateness or indication points, and the contextualizing the lessons into current situations. The study also concluded that both exegetes differed in some trends as Sayyid Qutb specifically addressed facts and perceptions about Islam. HAMKA, on the other hand, was different from Sayyid Qutb in the political direction, the ethical direction, and the explanation of jurisprudence rulings.